POTENTIAL USE OF TECHNOLOGY TO DEVELOP ELEMENTARY STUDENTS’ MATH SKILLS THROUGH TOON MATH - Arsika Putri; Muhamad Hanif; Tia Putri Ramadhani; Faradilla Nurhaliza; Adinda Febriyanti; Indah Mutiara; Silvi Kirani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Everyone needs to learn mathematics, which is a basic science. It is undeniable that the life of the world cannot be separated from mathematics. But, most elementary school students, unfortunately, are still difficult to count and lack interest in mathematics. Through this paper, the researcher aims to find out the elementary students’ arithmetical speed in grade 2 and to apply a quantitative approach by applying the pre-experimental design method, one group pretest-posttest type. The research results indicate that there was a significant increase. In the pretest, there were students who answered quickly and correctly on the summation questions, there were 32% students. Based on the subtraction questions, there were 22% of students. Based on the story summation questions, there were 43% of students. Based on the division questions, there were 13% of students. And based on multiplication, there were 51% of students. And these results increased in the post-test conducted by researchers, which students who answered quickly and correctly on summation questions at 84% of students, subtraction questions at 73% of students, story summation questions at 62% of students, division questions were 43% of students, and on multiplication questions 54% of students. The implication of this Toon Math application is that Toon Math can be used as a variation of mathematics learning so that students have an interest to learn mathematics. Based on the description of the data, it states that the Toon Math game influences the students’ increasing arithmetical speed.